Science Teacher’s Knowledge about Lesson Study as A Professional Investigation Approach in Learning - Natalia Rosa Keliat; Pradita Putri Anggraini; Jessica Ayu Trisianna (Postgraduate, University of Mataram, 2025)
Lesson study is a teacher collaborative approach to professional development. Lesson study is a model for fostering educator professionalism through collaborative and continuous learning assessments based on collegial and mutual learning principles to build learning communication. The aim of this research is to get an overview of science teachers' knowledge about lesson study as a professional inquiry approach in learning. Surveys of lesson study activities carried out by teachers can help to understand the characteristics of professional learning through effective lesson study and the extent to which teachers carry out and are involved in the lesson study process. The research was conducted in Salatiga, Central Java, Indonesia. This research method uses quantitative descriptive. The data collection technique uses a survey using a questionnaire as an instrument consisting of 70 statements from seven categories regarding lesson study. Respondents were science teachers selected using purposive sampling. Data analysis uses percentage techniques. Based on a survey conducted on science teachers regarding the implementation of lesson study, it is known that there are 5% of respondents who have never heard of lesson study, 30% of respondents have never been involved in lesson study activities, and there are around 40 % of respondents who have never carried out lesson study activities in teaching. Based on the seven categories of lesson study asked to teachers who have carried out lesson study in learning, it is known that there are still teachers who have weak motivation to improve the quality of learning, there are still science teachers who do not understand how to implement lesson study and how to use time in lesson study. Apart from that, it was found that science teachers still had a weak understanding of the benefits of lesson study in increasing teacher collaboration, the benefits of lesson study in improving the quality of teaching and learning, and there were still science teachers who did not understand how lesson study was started.